Strengthening Preventive Health Services in Urban Indonesia: A Qualitative Study from Puskesmas Kuta Alam - Arwan; Syam, Sadli; Firmansyah; Syahrir, Muhammad Sabri; Satria, Muhammad Aji; Hilintang, Rendhar Putri (Medicor : Journal of Health Informatics and Health Policy, 2025)
This study specifically examines how promotive and preventive health strategies are implemented in Puskesmas Kuta Alam, Banda Aceh, Indonesia, to address the challenges of urban health services. This study aims to explore the implementation dynamics of these strategies at Puskesmas Kuta Alam, an urban public health center in Banda Aceh, Indonesia. Using a qualitative descriptive approach, data were collected through interviews, observations, and document analysis, focusing on four themes: communication, resources, staff disposition, and bureaucratic structure. Findings reveal that while health promotion efforts exist, they are constrained by unidirectional communication practices, low community engagement, and a lack of culturally adapted messaging. Human resource limitations, including an absence of trained personnel and insufficient educational infrastructure, further weaken program effectiveness. Staff demonstrated moral commitment to preventive care but lacked formal training and policy literacy, leading to inconsistent implementation of national health regulations. Moreover, the absence of a clearly defined organizational structure for promotive preventive programs resulted in poor coordination and accountability. These insights highlight the systemic challenges faced by Puskesmas in Banda Aceh in translating health policy into practice. The study recommends adopting participatory communication strategies, enhancing training and infrastructure, and establishing a dedicated institutional unit for preventive services. By contributing to the growing body of knowledge on primary health care implementation in LMICs, the study offers evidence based recommendations to strengthen health promotion capacity at the local level.